Hydrated MgxV5O12 Cathode with Improved Mg2+ Storage Performance. Issue 45 (21st October 2020) - Zhu, Yunpei; Huang, Gang; Yin, Jun; Lei, Yongjiu; Emwas, Abdul‐Hamid; Yu, Xiang; Mohammed, Omar F.; Alshareef, Husam N.
Abstract: Mg‐ion batteries (MIBs) possess promising advantages over monovalent Li‐ion battery technology. However, one of the myriad obstacles in realizing highly efficient MIBs is a limited selection of cathode materials that can enable reversible, stable Mg 2+ intercalation at a high operating voltage. Here, a scalable method is showcased to synthesize a hydrated Mg x V5 O12 cathode, which shows a high capacity of ≈160 mAh g −1 with a high voltage of 2.1 V, a decent rate capability, and an outstanding cycling life (e.g., 81% capacity retention after 10 000 cycles). The combination of in situ and ex situ characterizations and first‐principles calculations provides evidence of reversible, facile topochemical Mg 2+ intercalation into the expanded 2D channels of the hydrated Mg x V5 O12 cathode, which results from the synergistic effects of Mg 2+ pillars and structural H2 O. The findings underscore the advantage of the rich but controllable chemistry of vanadium oxide bronzes in achieving practical multivalent cation mobility. Abstract : A near‐room‐temperature chemical method is developed to synthesize hydrated Mg x V5 O12 nanofibers with an expanded interlayer spacing. The structural water promotes Mg 2+ diffusion kinetics, while the Mg 2+ pillars enable a stable cathode framework. Through this synergistic effect, the hydrated Mg x V5 O12 nanofibers show remarkable rate capability and cycling stability.